Inhibitory effects of various solvent extracts from Rhamnus frangula leaves on some inflammatory and metabolic enzymes - Ben Bacha, Abir; Jemel, Ikram; Bhat, Ramesa Shafi; Onizi, Mona Awad (Cellular and Molecular Biology, 2018)
Many enzymes are involved in numerous pathologies which are related to metabolic reactions and inflammatory diseases such as pancreatic lipase, Î±-amylase, Î±-glucosidase and xanthine oxidase and secreted phospholipases A2 (Group IIA, V and X), respectively. Therefore, inhibiting these enzymes offer the potential to block production of more inflammatory substances and decrease the risk factors for cardiovascular diseases. The purpose of this study was to investigate some potent, bioavailable and selective inhibitors of some catalytic proteins implicated to metabolic syndrome and their antioxidant effects from various solvent extracts of R. frangula leaves. The anti-inflammatory, obesity, diabete and XO potentials were evaluated through analyses of inhibition activities of corresponding metabolites.The water extract exhibited an important inhibitory effect on human, dromedary and stingray sPLA2-G IIA achieved an IC50 of 0.16±0.06, 0.19±0.05 and 0.07±0.01 mg/mL, respectively. Likewise, the same fraction demonstrated the highest pancreatic lipase inhibitory activity using two different substrates. Indeed, 50% of dromedary pancreatic lipase inhibition was demonstrated for 5 min and 15 min using olive oil and TC4 substrates, respectively. Besides, it was established that methanolic extract had more effective inhibitory lipase activity than ORLISTAT used as a specific inhibitor of gastric, pancreatic and carboxyl ester lipase for treating obesity, with an IC50 of 5.51±0.27 and 91.46±2.3 µg/mL, respectively. In the case of Î±-amylase, Î±-glucosidase and xanthine oxidase, the crude methanolic extract showed a potential inhibitory effect with an IC50 of 45±3.45, 3±0.15 and 27±1.71 µg/mL, respectively. Conclusively, R. frangula leaves extracts showed a potential value of some sPLA2, some metabolic enzymes and XO inhibitors as anti-inflammatory and metabolic syndrome drugs.